Uji Efektivitas Ekstrak Buah Jeruk Nipis (Citrus aurantifolia) dalam Menghambat Pertumbuhan Bakteri Enterococcus faecalis Secara In Vitro - Annisa Fajriatul Arafah; Vivi Triana; Murniwati Murniwati (Andalas Dental Journal, 2015)
Enterococcus faecalis is a normal microorganism in root canal teeth, anaerobic facultative, and gram positive cocci. This bacteria is opportunistic that cause secunder infection in root canal. Lime (Citrus aurantifolia) is one of the plants which have antimicrobial activity because lime contains flavonoid and citric acid. Flavonoids can denature proteins in bacterial cell and damaging the cell membrane. Citric acid can damaging the bacterial cell wall and inhibiting bacterial enzymes activity. The purpose of this study was to examie the effectiveness lime extract in various concentration in inhibiting Enterococcus faecalis in in-vitro. The research method was experimental laboratories with posttest only control group design. Samples were used in this research are Enterococcus faecalis bacteria in M. Djamil’s Hospital Microbiology Laboratory, Padang. This research was conducted at organic chemistry of natural materials laboratory FMIPA UNAND and Kopertis Wilayah X Padang laboratory. Early stage was done by making extracts of lime with concentrations are 25%, 50%, 75%, and 100%. Then, the extracts was tested into the bacteria with the diffusion method used papper disk. The inhibition zone formed between lime extracts in various concentrations to the growth of Enterococcus faecalis were calculated using calipers. Data was analyzed by using Kruskal Wallis test and Mann-Whithney test with confidence interval of 95%. The result presented that 25%, 50%, 75%, and 100% lime extracts have inhibition activity in inhibiting the growth of Enterococcus faecalis, and the higher the concentration of the extracts, the greater the inhibition zone formed.